The influence of career development, organisational commitment and job satisfaction on employee performance regional secretariat of Sungai Penuh City - Wazirman Wazirman; Mahdalena Mahdalena; Hafdi Risman; Sulvia Dewi (Institute of Computer Science (IOCS), 2023)
This study aims to analyse the influence of career development, organisational commitment, and job satisfaction on the performance of employees of the regional secretariat of Sungai Penuh city in the context of the current work environment. This research uses a quantitative approach with a survey method, involving employees of the regional secretariat of the city of Sungai Penuh. The technique in sampling is using total sampling technique. The number of samples in this study was 45 people and hypothesis testing in this study using multiple linear regression analysis. The results of data analysis show that career development contributes positively to improving employee performance. Career development provides additional motivation for employees to improve their competence and contribute more effectively in achieving organisational goals. In addition, organisational commitment is also proven to have a positive effect on employee performance. Employees who have a high level of commitment tend to be more focused and dedicated in carrying out their tasks, which in turn has a positive impact on their performance. Furthermore, job satisfaction also has a positive influence on employee performance. Employees who feel satisfied with their jobs are more likely to work with high passion and dedication, and are more likely to achieve the results expected by the organisation. The results of this study suggest that career development, organisational commitment, and job satisfaction are key factors that play a role in improving employee performance. The findings of this study have important implications for human resource management and organisational leadership. Management needs to pay special attention to employee career development, develop strategies to increase organisational commitment, and create a work environment that supports employee job satisfaction. Thus, organisations can achieve better performance and create more productive and dedicated employees.